THE ABILITY OF TWO NICKEL-TITANIUM ROTARY SYSTEMS MADE OF DIFFERENT ALLOYS TO INDUCE DENTINAL RADICULAR MICROCRACKS - Irina Tsenova; Radosveta Vassileva; Emilia Karova (Peytchinski Publishing, 2019)
Purpose: The objective of the present study was to evaluate the ability of two nickel-titanium rotary systems made of different alloys to induce dentinal radicular microcracks Materials and methods: Thirty - six extracted lower incisors were included in the current in vitro experiment. The samples were randomly assigned into three equal groups (n=12): negative control, ProTaper Universal and HyFlex CM. Roots in the control group were left unprepared, and the other two were shaped by using ProTaper Universal and HyFlex CM files. After mechanical instrumentation of the root canals all specimens were horizontally sectioned at 3, 6, 9 mm from the apex and the occurence of dentinal microcracks was registered. Statistical analysis of the results was performed by Fisher's exact and chi-square tests (p < 0.05). Results: The samples from the control group remained intact. Both testes NiTi file systems induces dentinal defects. There was no statistically significant differences between ProTaper Universal and HyFlex CM. Defects in the apical region in both experimental groups were significantly more than those in the coronal and midportion of the roots. Conclusions: ProTaper Universal and HyFlex CM systems performed equally and resulted in dentinal defect formation regardless of their alloy type. More damages were registered in the root apical portion for both tested systems.